Innovation, Market Structure, and Firm Size - Acs, Zoltan J.; Audretsch, David B. (The Review of Economics and Statistics, 1987)
The hypothesis that the relative innovative advantage between large and small firms is determined by market concentration, the extent of entry barriers, the composition of firm size within the industry, and the overall importance of innovation activity is tested. The authors find that large firms tend to have the relative innovative advantage in industries that are capital intensive, concentrated, highly unionized, and produce a differentiated good. The small firms tend to have the relative advantage in industries that are highly innovative, utilize a large component of skilled labor, and tend to be composed of a relatively high proportion of large firms. Copyright 1987 by MIT Press.